Controversies in stroke - Davies, Stephen; Donnan, Geoffrey (Henry Stewart Talks, 2008)
Thunderclap headache with normal CT and LP, Further investigations are unnecessary, Patent foramen ovale and recurrent stroke, Closure is the best option, Extracranial arterial dissection, Anticoagulation is the treatment of choice
Archived at 2018/12/10